The role of cross-cultural competences in start-up companies - Tóth, Eszter, 1980- (2012)
The success of innovation and new ventures is a common interest of all spheres of society since they are drivers of economic development. However, growing international competition among firms, as well as the state of the global economy present difficulties that many new companies struggle with. Therefore it is important to learn more about new businesses in order to understand better their challenges and the environment they face. Cross-cultural competences refer to a person's effectiveness in an unfamiliar cultural setting, which has significance in interactions between individuals of differing cultural backgrounds. The tendency for increasing internationalisation of businesses triggers questions around the merits of cross-cultural competences of employees in start-up companies. The purpose of this study is to explore the role of cross-cultural competences in start-up companies in Iceland. The method of semi-structured interviews paired with observations of the researcher has been employed in a qualitative and exploratory study. Eleven employees in six Icelandic start-up companies participated in the research, whose interviews have been analysed, coded and discussed from a theoretical perspective. Conclusions of the study include that cross-cultural competences enable startups to benefit from the contributions of foreign workforce, help start-ups in understanding and responding to the needs of international markets as well as support new businesses in becoming a learning organisation. Additional benefits of cross-cultural competences include strengthened communication and enhanced relationships among employees and with customers. Árangur nýsköpunar- og sprotafyrirtækja er mikilvægur því þau auka efnahagslegan vöxt. En mörg fyrirtæki eiga erfitt með að fóta sig í vaxandi samkeppni á alþjóðlegum vettvangi og efnahagslegu ástandi í heiminum. Því er mikilvægt að rannsaka og skilja betur umhverfi og áskoranir sprotafyrirtækja. Alþjóðahæfni (cross-cultural competences) er mikilvæg til að hjálpa einstaklingum í ...